Finite-dimensionality and growth of algebras specified by polylinearly interrelated generators - Redchuk, I. K. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We investigate the finite-dimensionality and growth of algebras specified by a system of polylinearly interrelated generators. The results obtained are formulated in terms of a function $ρ$.